WAYS OF MANAGEMENT AND IMPLEMENTATION OF SMALL HYDROPOWER SYSTEMS BASED ON SMART WATER MONITORING THROUGH THE “SMART WATER” DEVICE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article considers the development, technical and economic justification, and practical implementation of a “Smart Water” device based on modern IoT technologies for the effective management of small hydropower systems. The device optimizes energy production by monitoring water flow, level, and pressure in real time. In the context of water scarcity problems in the world, this device is of great importance in the rational use of water resources, strengthening local energy infrastructure, and developing environmentally friendly energy sources.